KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMP MENGGUNAKAN PENDEKATAN MATEMATIKA REALISTIK INDONESIA - Rani Refianti; Putriana Putriana; Elya Rosalina (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2020)
This study aims to determine the ability of students to solve mathematical problems in mathematics learning using the Indonesian Realistic Mathematics Education Approach (PMRI). The data collection technique used the test technique which was analyzed using the t-test at the significant level α = 5%. From the results of the post-test students' problem solving abilities with indicators of understanding the problem by 93% were in the very good category, the indicators of making a completion plan were 73% in the good category, the indicators of implementing the plan were 65% in the good category and the indicators of checking the results were 25 % with less category. After participating in learning using the Indonesian Realistic Mathematics Education Approach (PMRI) the average post-test score was 70.35 with 5 excellent students, 12 good students and 6 good enough students.